Collection development and management for 21st century library collections : an introduction - Gregory, Vicki L., 1950- (New York : Neal-Schuman Publishers, 2011)
Covering virtually every aspect of its subject, Collection Development and Management for 21st Century Library Collections is a soup-to-nuts guide perfect for students and beginning librarians, yet full of sage advice and new ideas for experienced practitioners.
The impact of new technologies on collection development and management -- Assessing user needs and marketing the collection to those users -- Collection development policies -- Selection sources and processes -- Acquisitions -- Budgeting and fiscal management -- Assessment and evaluation of the collection, including deselection (weeding) -- Cooperative collection development and resource sharing -- Legal issues in collection development -- Professional ethics and intellectual freedom -- Preservation -- The future of collection development and management.
Includes bibliographical references and index.
System requirements for accompanying disc: Adobe Reader; Microsoft Excel; CD-ROM drive.
Keywords: Collection management (Libraries); Collection management (Libraries) -- United States; Collection development (Libraries); Collection development (Libraries) -- United States; Acquisitions documentaires; Documents; Bibliothèques; Bibliothéconomie; Collection development (Libraries); Collection management (Libraries); Bibliotheekcollecties; Collectievorming; Toekomstverwachtingen; Bibliotheksbestand; Bestandsaufbau; Management; Beståndsutveckling (bibliotek); Bibliotekssamlingar; United States; USA; Books with discs; Nonfiction; CD-ROMs.